Developing and applying a smart city for development model: the case of COR in Rio de Janeiro - Kuhl, Alexander (2018)
Purpose: The present thesis addresses how smart city initiatives can positively impact development, with a special emphasis on developing countries in Latin America. Existing definitions and maturity models have a very strong focus on the mere use of Information and Communication Technology (ICT) and ignore the special needs and factors to be considered in developing countries. Methodology: By using the extant literature on Smart Cities and Information and Communication Technology for Development (ICT4D) as a related area from which to learn, a comprehensive Smart City for Development (SC4D) model is introduced and then exemplified via its application to a Latin American smart city initiative. Findings: The thesis argues that a favorable ecosystem for SC4D is one that is backed by both national and local sustainability, infrastructure, human capital, services, apps, and data. Practical implications: Successful SC4D initiatives include bottom-up approaches, citizen participation, a fit with both the national and the local culture, as well as a fit with the United Nations’ Sustainable Development Goals and the Capability Approach developed by Amartya Sen.